Історія міста Коломия у протидії дезінформаційним викликам - Зварич, Роман Васильович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
At the beginning of 2023 year, a new academic discipline “History of the Native Land” was launched at the Kolomyia Pedagogical Professional College of the Ivano-Frankivsk Regional Council at the initiative of Director V. Kovtun. During the genocide against the Ukrainian nation and the growth of hybrid threats, the preservation of national memory, in particular the local history of the Kolomyia region, plays an important role. The students of college are able to clearly identify themselves as belonging to the great Ukrainian nation on the basis of the historical facts of their native land in order to prevent anti-Ukrainian sentiments and to strengthen the Ukrainian state. The history of the native land is taught by the Ph. D. R. Zvarych.